Effect of Temperature on Foaming Ability and Foam Stability of Typical Surfactants Used for Foaming Agent. Issue 3 (24th March 2017) - Wang, Hetang; Guo, Wangbiao; Zheng, Chuanbao; Wang, Deming; Zhan, Hanhui
Abstract: Foam has extensive applications in a wide range of industrial fields. Some surfactants are used as foaming agents in the preparation of foam. The performance of the foaming agent directly affects the application of the foam. In this paper, experiments were designed and conducted to reveal the influence of temperature on foaming performance of 10 typical anionic, cationic, nonionic, and amphiprotic surfactants. They were exposed to different temperature conditions to measure the foaming capacity (FC), foaming expansion (FE), and foam's half‐life. FC and FE represent foaming ability (FA), and half‐life represents foam stability (FS). The results show that the FC increased at elevated foaming temperature, while FS decreased with rising temperature. Anionic surfactants are less affected by temperature and have better FA and longer FS. It seems that 20–30 °C is an ideal foaming temperature. This study lays an important foundation for the efficient preparation and utilization of foam in industrial fields.